The Influence of Service Quality and Facilities on Revisit Intention at Aufa Hotel with Customer Satisfaction as an Intervening Variable - Fitri Wahyuni; Fita Kurniasari (SAINTIS Publishing, 2025)
This study aims to analyze the influence of service quality and facilities on revisit intention at Aufa Hotel, with customer satisfaction as an intervening variable. The research is based on the importance of maintaining customer loyalty amid increasingly competitive conditions in the hospitality industry, particularly in plantation-based economic areas such as Manis Mata District, Ketapang Regency, West Kalimantan. This study employs a quantitative associative approach, with data collected through questionnaires distributed to 100 respondents who had stayed at Aufa Hotel at least twice. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The results indicate that both service quality and facilities have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction significantly influences revisit intention and also mediates the relationship between service quality and facilities with revisit intention. These findings suggest that consistently improving service quality and facilities plays a crucial role in shaping positive customer experiences and fostering customer loyalty.